2008
DOI: 10.1002/sia.2984
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of molybdate–benzotriazole surface treatment against copper tarnishing

Abstract: The synergistic effect of benzotriazole (BTAH) and molybdate on the inhibition of copper tarnish was studied in this paper. The antitarnish treatment of copper was conducted with BTAH solution containing molybdate. The surface morphology observation and composition analysis were investigated by SEM with energy dispersive X-ray (EDX) spectroscopy. The addition of molybdate improved the protection of BTAH significantly. The BTAH + molybdate treated copper specimen has higher N concentration in its surface. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…7(a) shows the element depth profiles of the ruthenium surface under a pH 6 condition. After 20 min, the Ru atomic concentration increases to greater than 90%, and the film thickness is thereby estimated to about 80 nm [41]. Fig.…”
Section: Surface Passivation Characterizationmentioning
confidence: 99%
“…7(a) shows the element depth profiles of the ruthenium surface under a pH 6 condition. After 20 min, the Ru atomic concentration increases to greater than 90%, and the film thickness is thereby estimated to about 80 nm [41]. Fig.…”
Section: Surface Passivation Characterizationmentioning
confidence: 99%
“…Silyl ester [38,39], silanes [117,[160][161][162], mercapto compounds [149,159], azolesparticularly benzotriazole [163][164][165][166][167] prevention, with some listed in Table 8.2. The key to a successful design is to find a good inhibitor system with the correct solubility.…”
Section: Inhibitor Requirementsmentioning
confidence: 99%
“…In XPS analysis ( Figure 6), all of the groups (irrespective of Na 2 MoO 4 content) contained C 1s, N 1s, O 1s, Cu 3d, Cu 3p 1/2, Cu 3s and Cu 2p 1/2 peaks. The C, N, O elements were components of the BTA and the peaks related to Cu-BTA formation [25]. When 1 mM Na 2 MoO 4 was added, Mo-related peaks were not detected in the surface components (binding energy = 228 eV: Mo 3d 5/2, 231 eV: Mo 3d 3/2, Figure 6(b1)), suggesting that Na 2 MoO 4 was involved in the formation of the Cu-BTA film but was not itself part of the chemical bonding [25].…”
Section: Surface Morphology Analysismentioning
confidence: 99%
“…Increasing the amount of Na 2 MoO 4 (i.e., over 5 mM) did not affect the rate of corrosion, because Na 2 MoO 4 at 0.01 M concentration in the electrolyte represents a critical quantity for stable passivation [32]. The presence of molybdate results in the passivation of copper, which enhances the adsorption of BTA [25]. Moshier et al [33] showed that both the Mo +4 and Mo +6 states is limited by solubility and the molybdate had been reduced during the formation of the passive film.…”
Section: Characterization Of Electro-chemical Corrosionmentioning
confidence: 99%
See 1 more Smart Citation